The Relative Effectiveness of Spot and Derivatives Based Intervention - Milan Nedeljkovic; Christian Saborowski (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies the relative effectiveness of foreign exchange intervention in spot and derivatives markets. We make use of Brazilian data where spot and non-deliverable futures based intervention have been used in tandem for more than a decade. The analysis finds evidence in favor of a significant link between both modes of intervention and the Real/Dollar exchange rate return. In line with theory, the impact of spot market intervention is strikingly similar to that achieved through futures based intervention worth an equivalent amount in notional principal when convertibility risk is limited. We show that both types of interventions also affect the level and the price of hedging risk in the foreign exchange market.
Keywords: F31; G10; E50; 330; FX intervention; derivatives; exchange rates